2015 Global hunger index by severity - von Grebmer, Klaus; Bernstein, Jill; de Waal, Alex; Prasai, Nilam; Yin, Sandra; Yohannes, Yisehac (Welthungerhilfe, 2015)
The Global Hunger Index (GHI) is based on four component indicators: >> UNDERNOURISHMENT: the proportion of undernourished people as a percentage of the population (reflecting the share of the population with insufficient caloric intake); >> CHILD WASTING: the proportion of children younger than age five who suffer from wasting (low weight for their height, reflecting acute undernutrition); >> CHILD STUNTING: the proportion of children younger than age five who are stunted (low height for their age, reflecting chronic undernutrition); and >> CHILD MORTALITY: the mortality rate of children younger than age five (partially reflecting the fatal synergy of inadequate nutrition and unhealthy environments). Combining the proportion of undernourished in the population with the indicators relating to children under age five ensures that both the food-supply situation of the population as a whole and the effects of inadequate nutrition on a physiologically very vulnerable group are captured. Children’s nutritional status deserves particular attention because a deficiency of nutrients places them at high risk of physical and mental impairment and death. For many children in developing countries who die from infectious diseases, the indirect cause of death is a weakened immune system due to a lack of dietary energy, vitamins, and minerals. Since the first three indicators—the proportion of undernourished and the prevalence of wasting and stunting in children—do not capture premature death as the most tragic consequence of hunger, the under-five mortality rate is also included. The Global Hunger Index goes beyond dietary energy availability to reflect the multidimensional causes and manifestations of hunger. Inequitable resource allocations between households and within households are also taken into consideration since the latter affect the physical well-being of children. Sufficient food availability at the household level does not guarantee that all members benefit from it in equal measure. The GHI varies between the best possible score of 0 and the worst possible score of 100. Higher scores indicate greater hunger— the lower the score, the better the country’s situation. GHI scores above 20 are considered serious, scores greater than 35 are alarming, and scores exceeding 50 are extremely alarming. The calculation of GHI scores is restricted to countries where measuring hunger is considered most relevant. Some higher-income countries are not included because hunger has been largely overcome in these countries and overnutrition is a greater problem than a lack of food.